The Persistence of Polymorphisms across Species Radiations. (September 2020) - Jamie, Gabriel A.; Meier, Joana I.
Abstract : Studies on polymorphisms have been foundational to our understanding of evolution. The presence of different phenotypic morphs is sometimes considered a precursor to speciation in which morphs evolve into different species. While speciation should initially reduce genetic variation in daughter versus parental species, a common pattern is the recurrence of the same phenotypic polymorphism in many species of a clade. Despite the ubiquity of these persistent polymorphisms, there is little discussion of their evolutionary origins. How does the genetic variation underpinning such polymorphisms cross speciation boundaries? What selection pressures maintain the morphs in multiple daughter species? Using diverse case studies, we highlight the characteristics of polymorphisms and selection regimes influencing the likelihood of polymorphism retention across species radiations. Highlights: The same intraspecific polymorphism is often found in many closely related species. Polymorphism recurrence across species radiations requires both that the genetic variation underpinning the polymorphism and the balancing selection regime persists through speciation. Disassortative mating among morphs facilitates their retention across speciation bottlenecks by increasing the likelihood both of polymorphism inheritance and maintenance. Nonecological, negative frequency-dependent selection is particularly likely to promote polymorphism persistence across species radiations because it increases the probability that the balancing selection operating in the parental species continues to operate in the daughter species even when they differ in their ecology. Rapid species radiations may be particularly prone to recurrent polymorphisms because lost morphs are easily reintroduced through introgression.